How Does Knowledge Absorption Foster Performance? The Mediating Effect of Innovation Capability - Heru Sulistyo; Sri Ayuni (Jurnal Dinamika Manajemen)
This research aims to examine the impact of knowledge sharing and knowledge absorption on the innovation capability and the performance of Sharia banks. The rapid competition in banking industry among conventional and Sharia banks requires innovation capability in order to enhance the performance and achieve the sustainable competitive advantage. The development and performance of Sharia banks at the present still tend to be low. Innovation on product and service is one of the success keys of Sharia banks in enhancing the performance and competitiveness. Innovation capability can be developed if the employees within the organization are able to perform knowledge sharing or knowledge absorption. The sample of this research includes the employees of Sharia Banks in Semarang as many as 102 respondents. The sampling technique uses purposive sampling with criteria; permanent employees who have been working no less than 5 years. The data collection method is performed using questionnaire, while the data analysis technique uses SEM. The finding concludes that knowledge sharing and knowledge absorption significantly impact the innovation capability and performance.